Theoretical study on photocatalytic performance of ZnO/C2N heterostructure towards high efficiency water splitting - Liu, Meiping; Tang, Yong; Yao, Haizi; Bai, Liuyang; Song, Jun; Ma, Benyuan (Frontiers in Chemistry, 2022)
Constructing van der Waals heterostructures is an effective scheme to boost the photocatalytic performance of two-dimensional material. In this work, the electronic and absorption properties of emerging ZnO/C2N heterostructure have been systematically studied to explore its photocatalytic potential by using the first-principles method. Results demonstrate that ZnO and C2N form a type-II band alignment heterostructure with reduced band gap, and the heterostructure exhibits superior absorption in the visible region. Besides, the band edge positions of ZnO/C2N heterostructure meet with the requirements for spontaneous water-splitting. Particularly, ZnO/C2N heterostructure has been confirmed to possess several times improved carrier mobilities, which is advantageous to the separation and migration of carriers. Gibbs free energy calculation indicates the high catalytic activity of ZnO/C2N heterostructure for water splitting reactions. All the above properties, including band gap, band edge positions, optical absorption, can be directly tuned by biaxial lateral strain. The suitable bandgap, decent band edge positions, high catalytic activity and superior carrier mobility enable ZnO/C2N heterostructure as a prominent candidate photocatalyst for water splitting.